Use Of Discrete Fiber In Road Construction - Gull, Ifrah; Vikram, Er. Ajay (Journal of Neonatal Surgery, 2025)
Concrete roads are widely used due to their durability, smooth surface, and low maintenance requirements; however, they are prone to cracking, spalling, and have limited tensile strength and ductility. To address these limitations, this study titled "The Use of Discrete Fiber in Road Pavements" investigates the effect of incorporating polypropylene and polyester fibers into M25 grade concrete. Four types of specimens were tested: plain concrete, concrete with 1.8% polypropylene fiber, with 0.5% polyester fiber, and a combination of both fibers. Each sample was evaluated for compressive, flexural, and split tensile strength. The results showed a notable improvement in all strength parameters with fiber inclusion, indicating that discrete fiber reinforcement significantly enhances the performance of concrete pavements.